+0  
 
0
222
1
avatar+176 

https://vle.mathswatch.co.uk/images/questions/question689.png

jakeharris02  Oct 7, 2017
 #1
avatar+87691 
+1

3x^2  - 3x + 2  = 2    subtract 2 from both sides

 

3x^2 - 3x  =  0         this shifts the graph of  3x^2 - 3x -1  up one unit

 

So   3x^2 - 3x  =  0   at x = 0  and x = 1

 

 

 

3x^2 - 3x -1  =  x + 1

 

The graph of x + 1  would intersect 3x^2 - 3x -1   at  x ≈ -4/10   and  x ≈ 1.5

 

 

cool cool cool

CPhill  Oct 7, 2017

31 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.